10−7 m 17β‐oestradiol enhances odonto/osteogenic potency of human dental pulp stem cells by activation of the NF‐κB pathway. (24th October 2013) - Wang, Y.; Zheng, Y.; Wang, Z.; Li, J.; Wang, Z.; Zhang, G.; Yu, J.
Abstract: Objectives: Oestrogen has been proven to significantly enhance osteogenic potency, while oestrogen deficiency usually leads to impaired osteogenic differentiation of mesenchymal stem cells. However, little is known concerning direct effects of oestrogen on differentiation of human dental pulp stem cells (DPSCs). Materials and methods: In this study, human DPSCs were isolated and treated with 10 −7 m 17β‐oestradiol (E2). Alkaline phosphatase (ALP) assay and alizarin red staining were performed. Results: Alkaline phosphatase and alizarin red showed that E2 treatment significantly enhanced ALP activity and mineralization ability of DPSCs, but had no effect on cell proliferation. Real‐time RT‐PCR and western blot assay demonstrated that odonto/osteogenic markers ( ALP, RUNX2 /RUNX2, OSX /OSX, OCN /OCN and DSPP /DSP) were significantly upregulated in the cells after E2 treatment. Moreover, phosphorylation of cytoplasmic IκBα/P65 and expression of nuclear P65 were enhanced in a time‐dependent manner following E2 treatment, suggesting activation of NF‐κB signaling. Conversely, inhibition of the NF‐κB pathway suppressed E2‐mediated upregulation of odonto/osteogenic markers, indicating that the NF‐κB pathway was pivotal for E2‐mediated differentiation. Conclusion: These findings provide evidence that 10 −7 m 17β‐oestradiol promoted odonto/osteogenic differentiation of human DPSCs via activation of the NF‐κB signaling pathway.